Improving Speed Reading Proficiency using Scanning Technique for Grade VII Students at SMP Negeri 81 Maluku Tengah - Teka, Kristina; Parinussa, Jolanda Dessye (Universitas Pattimura, 2025)
Students possessing rapid reading skills but deficient in comprehension speed will undoubtedly experience a decline in reading efficacy. The reading speed of students is significantly influenced by their interest in the content to be comprehended. This research aims to enhance the speed reading proficiency of 7th-grade students at SMP Negeri 81 Maluku Tengah through the application of the scanning approach. This study constitutes classroom action research. The employed data collection methods include observation, questionnaires, interviews, and documentation. Researchers reached the following conclusions, among others: The implementation of the scanning methodology for seventh-grade students at SMP Negeri 81 Maluku Tengah rendered studying more engaging and entertaining, while also facilitating the development of their extensive and methodical reading skills. The scanning technique fostered an engaging environment, enabling each student to develop knowledge and experience in quick reading skills. Prior to the implementation of this scanning technique, the average reading speed of 7th-grade pupils at SMP Negeri 81 Maluku Tengah was 35. Following the implementation of this technique in Cycle I, the average score increased to 46, reflecting a 10.8% rise; nevertheless, further improvement is anticipated in Cycle II. The execution of Cycle I had numerous deficiencies, including: 1) pupils continued to struggle with time management, reading velocity, and comprehension proficiency. Only seven pupils achieved the Minimum Competency Criteria (MCC). The deficiencies were rectified in Cycle II. Cycle II results indicated an enhancement in students' reading speed, with a class average score of 75 and 17 pupils achieving the MCC norm. In conclusion, the implementation of rapid reading skills using the scanning technique is highly successful in enhancing students' speaking abilities, particularly their rapid reading skills.